THE RHYTHM OF REORGANIZING THE WORLD. MALDINEY AND THE THEORY OF CRISIS - Yasuhiko MURAKAMI (Studia Universitatis Babeș-Bolyai. Philosophia)
This article examines the work of French phenomenologist Henri Maldiney (1912-2013), a philosopher who shed light on the phenomenon of interrogation by a world that has lost its pre-existing coordinates. While Maldiney himself referred to paintings and mental illness, we try to read his theory as an analysis of social situation and action. His theory helps us understand end-of-life situations in which caregivers encounter scenes where it is difficult to break out of a stalemate. It is a theory of practice based on an innovative understanding of the concept of rhythm.